Eksplorasi Bakteri yang Berasosiasi dengan Karang Lunak sebagai Alternatif Sumber Senyawa Bioaktif: Uji Hayati Antibakteri - Esti Harpeni (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
Soft coral has a significant function in the ecology of coral reef which produces secondary metabolites. One of very serious problems with coral reef ecosystem related to secondary metabolite improvement was coral supply because of need of many soft corals producing a little amount of secondary metabolites. The purposes of this research were to isolate and to select soft coral bacteria that have ability to produce antibacterial having been used to inhibit Escherichia coli and Staphylococcus aureus. The research was conducted from March 31th to November 2nd, 2005 by using description method. Sampling was carried out at Pulau Tegal Waters on two different coral genera, namely Briareum and Sinularia at three different sites. Laboratory studies were performed at Environment and Healthy Monitoring Fish Laboratory at Lampung Marine Agricultural. The results showed that five of 125 isolates obtained had potential of producing antibacterial that have been used to inhibit E.coli and S. aureus. The coral ability to inhibit E.coli and S. aureus was indicated by inhibition zone around soft coral bacteria colonies. Morphology and biochemistry characterization of potentially inhibiting isolates against E. coli and S. aureus resulted in strains Staphylococcus sp. (isolate code B1I10), Plesiomonas sp. (isolate code B1I11), Actinobacillus sp. (isolate code B2I6), Actinomyces sp. (isolate code B1II4), and Aerococcus sp. (isolate code S1III2).